The effectiveness training programs for staff Malaysia Airports Holdings (MAHB) / Nuru Ain Abd Malik - Abd Malik, Nuru Ain (Faculty of Business and Management, 2010)
If we can see right now, many organization need to practice the training program in their organization no matter that company big or small. This is because, with training program, a lot of benefit that company and also their staff will get. For example, with the training program,it will increase the level of skill and gain more new knowledge.For this project paper tries to study on the effectiveness training pogram for staff Malaysia Airports Holdings Berhad (MAHB).This is an exploratary study that tries to identify the effectiveness among the staff after attending the training program. The study can also find which groups are strong and weak against the 4 independent variables.The 5 independent variables are the content evaluation,trainer evaluation,facilities evaluation.training support evaluation and also training effectiveness. Towards this weakness the study can suggest a better recommendation to overcome the weaknesses. After the analysis the research found that the respondent effectiveness of the training program is moderate among the respondent. Based on the finding the study gives appropriate recommendation to overcome the weakness towards the new process. For conclusion all the objective in this study has being met.